Physician career satisfaction within specialties - Kravitz Richard L; Tancredi Daniel J; Leigh J Paul (BMC, 2009)
Abstract Background Specialty-specific data on career satisfaction may be useful for understanding physician workforce trends and for counseling medical students about career options. Methods We analyzed cross-sectional data from 6,590 physicians (response rate, 53%) in Round 4 (2004-2005) of the Community Tracking Study Physician Survey. The dependent variable ranged from +1 to -1 and measured satisfaction and dissatisfaction with career. Forty-two specialties were analyzed with survey-adjusted linear regressions Results After adjusting for physician, practice, and community characteristics, the following specialties had significantly higher satisfaction levels than family medicine: pediatric emergency medicine (regression coefficient = 0.349); geriatric medicine (0.323); other pediatric subspecialties (0.270); neonatal/prenatal medicine (0.266); internal medicine and pediatrics (combined practice) (0.250); pediatrics (0.250); dermatology (0.249);and child and adolescent psychiatry (0.203). The following specialties had significantly lower satisfaction levels than family medicine: neurological surgery (-0.707); pulmonary critical care medicine (-0.273); nephrology (-0.206); and obstetrics and gynecology (-0.188). We also found satisfaction was significantly and positively related to income and employment in a medical school but negatively associated with more than 50 work-hours per-week, being a full-owner of the practice, greater reliance on managed care revenue, and uncontrollable lifestyle. We observed no statistically significant gender differences and no differences between African-Americans and whites. Conclusion Career satisfaction varied across specialties. A number of stakeholders will likely be interested in these findings including physicians in specialties that rank high and low and students contemplating specialty. Our findings regarding "less satisfied" specialties should elicit concern from residency directors and policy makers since they appear to be in critical areas of medicine.